High-temperature-resistant cable and preparation method thereof
By using nano-aluminum silicate fibers and modified nano-titanium dioxide and other materials in the cable, a dense flame retardant structure is formed, which solves the high-temperature resistance performance of the cable in a high-temperature environment. The poor problem significantly improves the flame retardant effect and fire safety.
Patent Information
- Application Number
- CN202411305231.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cables have poor high temperature resistance in high temperature environments and are not dense enough in flame retardant, resulting in insufficient fire safety.
Adopt an interior-to-out structure design, including cable core, flame retardant layer and sheath layer. The sheath layer is coated with a high-temperature protection coating, and nano-aluminum silicate fibers and modified nano-titanium dioxide are added to the coating, combined with glass The fibers and silicon carbide fibers are filled with layers to form a dense mesh structure to improve flame retardant properties.
It significantly improves the high temperature resistance and flame retardant performance of the cable, forms a uniform network structure, enhances the flame retardant effect, and achieves higher fire safety.
Smart Images

Figure CN119132724A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a high temperature resistant cable and a preparation method thereof. Background Art
[0002] Cable is a wire or cable used to transmit power, signals or data. They are widely used in power systems, including power plants, transmission systems, distribution systems and final power terminals. Power cables can carry currents of different voltage levels, from low-voltage household cables to high-voltage long-distance transmission cables. With the frequent occurrence of fire accidents, people's awareness of fire safety has increased, and the high temperature resistance and flame retardancy of wires and cables have become the focus of public attention. Therefore, higher requirements are put forward for the preparation of cables.
[0003] Chinese invention patent CN117894517B discloses a high temperature resistant and aging resistant cable and its preparation method, the cable includes a cable sheath and a conductor material wrapped by the cable sheath; the sheath is provided with an insulating layer, a high temperature resistant layer and an aging resistant layer from the inside to the outside, wherein the insulating layer is coated with a high temperature resistant layer on the outside, and the high temperature resistant layer is coated with an aging resistant layer on the outside; the high temperature resistant layer is filled with expanded graphite material, and the aging resistant layer is filled with hydrophobic fiber material, which has a simple structure, is easy to process, and has excellent mechanical properties, waterproofness, aging resistance and high temperature resistance, and has a long service life. Although expanded graphite is used to improve the high temperature resistance and flame retardant properties of the cable, however, expanded graphite alone may expand excessively when heated, that is, the "popcorn effect", and the carbon layer is loose and not dense enough, resulting in the flame retardant effect not meeting expectations.
[0004] Chinese invention patent CN117603518B discloses a fire-resistant flame-retardant cable, including several conductors arranged in sequence from the inside to the outside, the conductor surface is coated with an insulating layer, a tape layer is arranged outside the insulating layer, the insulating layer and the protective layer are both made of flame-retardant resin, a filler is filled between the tape layer and the insulating layer, and the outer surface of the wrapped inner lining layer is coated with a protective layer, and the flame-retardant resin includes the following raw materials by weight: EVA 40-50 parts, PE 120-150 parts, calcium carbonate 6-8 parts, modified flame retardant 4-6 parts and diisopropylbenzene peroxide 1-3 parts, which decomposes into polyphosphoric acid substances during combustion and can be dehydrated into carbon, thereby forming a carbon layer coated on the cable surface to isolate oxygen and heat. However, once the polyphosphoric acid substances produced by combustion and decomposition are unevenly distributed on the cable surface, they lose their flame-retardant effect. Summary of the invention
[0005] In view of this, an object of the present invention is to provide a high temperature resistant cable and a preparation method thereof, so as to solve the problem that the current cables have poor high temperature resistance performance.
[0006] Based on the above purpose, the present invention provides a high temperature resistant cable, which includes a cable core, a flame retardant layer and a sheath layer from the inside to the outside; the cable core is composed of multiple insulated wire cores arranged in parallel and longitudinally in a high temperature resistant filling layer, and the surface of the insulated wire core is in close contact with the high temperature resistant filling layer and is coated in the high temperature resistant filling layer; the insulated wire core includes a cable obtained by winding a plurality of wires, and an insulating layer coated on the outside of the cable; Wherein, the sheath layer also includes a high temperature resistant protective coating coated on its outer surface; and the high temperature resistant protective coating includes the following raw materials in parts by weight: 30-50 parts of acrylic emulsion, 25-40 parts of ammonium polyphosphate, 10-15 parts of pentaerythritol, 1-5 parts of nano aluminum silicate fiber, 5-10 parts of modified nano titanium dioxide, 1-5 parts of nano silicon dioxide, 0.5-2 parts of dispersant, 0.5-1 parts of plasticizer, and 0.01-0.1 parts of preservative; Wherein, the modified nano titanium dioxide preparation method comprises the following steps: S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, put it in a polytetrafluoroethylene reactor. Under sealed conditions, put it in an oven at 220-250° C. and heat it for 2.5-3 hours. After cooling, filtering and centrifugation, obtain nano-titanium dioxide crystal particles; S2. Wash the nano-titanium dioxide crystal particles obtained in step S1 with ethanol, then add them into a butyl acetate solution mixed with a silane coupling agent KH-540, and heat them at 65-80° C. for 20-30 min to obtain modified nano-titanium dioxide.
[0007] Furthermore, the mass ratio of the nano aluminum silicate fiber to the modified nano titanium dioxide is 1-2:2-6.
[0008] Furthermore, the thickness of the high temperature resistant protective coating is 3-5 mm.
[0009] Furthermore, the high temperature resistant filling layer includes glass fiber and silicon carbide fiber; the mass ratio of the glass fiber to the silicon carbide fiber is 10-5:5-3.
[0010] Furthermore, the glass fiber has a length of 1-3 mm, and the silicon carbide fiber has a length of 50-100 μm.
[0011] Furthermore, the insulating layer is cross-linked polyethylene.
[0012] Furthermore, the flame retardant layer comprises the following raw materials in parts by weight: 40-50 parts of silicone resin, 20-30 parts of high-density polyethylene, 10-15 parts of ethylene-octene copolymer, 5-10 parts of magnesium hydroxide, and 30-40 parts of glass fiber.
[0013] Furthermore, the sheath layer comprises the following raw materials in parts by weight: 50-70 parts of polyvinyl chloride resin, 5-10 parts of polyurethane elastomer, 20-25 parts of dioctyl phthalate, 25-30 parts of filler, 8-10 parts of stabilizer, 1-3 parts of antioxidant, 1-3 parts of anti-aging agent, and 0.5-1 parts of lubricant; the degree of polymerization of the polyvinyl chloride resin is 1800-2200.
[0014] Furthermore, the thickness of the flame retardant layer is 1-1.5 mm; the thickness of the sheath layer is 0.5-1 mm.
[0015] The present invention also provides a method for preparing the above-mentioned high temperature resistant cable, comprising the following steps: S1. Extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S2, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber to prepare a high temperature resistant filling layer; wherein the mass ratio of the glass fiber to the silicon carbide fiber is 10-5:5-3, and a cable core is obtained after the filling is completed; S3, mixing silicone resin, high-density polyethylene, ethylene-octene copolymer, magnesium hydroxide and glass fiber uniformly, kneading and extruding at 280-310° C., with the extruder speed being 40-50 rpm, and coating the cable core to obtain a flame retardant layer; S4, mixing polyvinyl chloride resin, polyurethane elastomer, dioctyl phthalate, filler, stabilizer, antioxidant, anti-aging agent and lubricant uniformly, kneading and extruding at 180-200° C., with the extruder rotating speed being 40-50 rpm, and coating the flame retardant layer to obtain a sheath layer; S5. When the surface temperature of the sheath layer drops to 30-40°C, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer, and then irradiate the sheath layer with ultraviolet light at an intensity of 90-150W / cm 2 The irradiation time is 1-2h, and high temperature resistant cables are obtained after irradiation.
[0016] Beneficial effects of the present invention: The present invention provides a high temperature resistant cable and a preparation method thereof, which comprises a cable core, a flame retardant layer and a sheath layer from the inside to the outside, wherein the sheath layer also comprises a high temperature resistant protective coating coated on its outer surface, and the high temperature resistant protective coating improves the raw material composition of the flame retardant coating commonly used in the prior art, and adds nano aluminum silicate fiber and modified nano titanium dioxide, and in a high temperature environment, the aluminum silicate fiber and titanium dioxide are sintered under the action of ammonium polyphosphate to obtain titanium silicon aluminum phosphate, and the titanium silicon aluminum phosphate forms a dense mesh structure, which is wrapped outside the sheath layer to isolate the air, and further achieves the purpose of flame retardancy. In addition, the nano titanium dioxide in the present invention is modified to improve the dispersibility and uniformity of distribution, so that the aluminum silicate fiber and titanium dioxide are more evenly fused, so that the network-like titanium silicon aluminum phosphate obtained by sintering the two is more evenly wrapped outside the sheath, achieving a better flame retardant effect.
[0017] The present invention provides a high temperature resistant cable and a preparation method thereof, wherein the cable core also includes a high temperature resistant filling layer. The high temperature resistant filling layer of the present invention adopts glass fiber and silicon carbide fiber, wherein glass fiber with a length of 1-3 mm and silicon carbide fiber with a length of 50-100 μm are mixed, the longer glass fiber forms a skeleton, and the shorter silicon carbide fiber is filled into the longer glass fiber skeleton, so that the filling layer is more compact; and the silicon carbide fiber has extremely excellent high temperature resistance and high temperature oxidation resistance, and is used in combination with the glass fiber to further improve the high temperature resistance of the filling layer.
[0018] The present invention provides a high temperature resistant cable and a preparation method thereof, which improves the high temperature resistance and flame retardancy of the cable, and the preparation method is simple, improves production efficiency, and can realize large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required to be used in the embodiments or the description of the prior art are briefly introduced below.
[0020] Figure 1 This is a schematic structural diagram of a high temperature resistant cable prepared in Example 1 of the present invention; The markings in the figure are: 1. High temperature resistant protective coating; 2. Sheath layer; 3. Flame retardant layer; 4. High temperature resistant filling layer; 5. Insulation layer; 6. Cable. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with specific embodiments. The present invention provides these embodiments to make the present invention thorough and complete, and to fully express the scope of the present invention to those skilled in the art. It should be noted that unless otherwise specifically stated, the relative arrangement of the parts and steps, the composition of the materials, the numerical expressions and the numerical values described in these embodiments should be interpreted as merely exemplary, rather than as limiting.
[0022] The embodiment of the present invention provides a high temperature resistant cable, which includes a cable core, a flame retardant layer and a sheath layer from the inside to the outside; the cable core is composed of a plurality of insulating cores arranged in parallel and longitudinally in a high temperature resistant filling layer, the surface of the insulating core is in close contact with the high temperature resistant filling layer and is coated in the high temperature resistant filling layer; the insulating core includes a cable obtained by winding a plurality of wires, and an insulating layer coated on the outside of the cable; wherein the sheath layer also includes a high temperature resistant protective coating coated on its outer surface, and the coating thickness is 3-5mm; and the high temperature resistant protective coating includes the following weights: The raw materials are as follows: 30-50 parts of acrylic emulsion, 25-40 parts of ammonium polyphosphate, 10-15 parts of pentaerythritol, 1-5 parts of nano aluminum silicate fiber, 5-10 parts of modified nano titanium dioxide, 1-5 parts of nano silicon dioxide, 0.5-2 parts of dispersant, 0.5-1 parts of plasticizer and 0.01-0.1 parts of preservative; wherein the mass ratio of nano aluminum silicate fiber to modified nano titanium dioxide is 1-2:2-6, and more preferably, the mass ratio of nano aluminum silicate fiber to modified nano titanium dioxide is 1:2.
[0023] In the embodiment of the present invention, the method for preparing modified nano titanium dioxide comprises the following steps: S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, put it in a polytetrafluoroethylene reactor. Under sealed conditions, put it in an oven at 220-250° C. and heat it for 2.5-3 hours. After cooling, filtering and centrifugation, obtain nano-titanium dioxide crystal particles; S2. Wash the nano-titanium dioxide crystal particles obtained in step S1 with ethanol, then add them into a butyl acetate solution mixed with a silane coupling agent KH-540, and heat them at 65-80° C. for 20-30 min to obtain modified nano-titanium dioxide.
[0024] Aluminum silicate and titanium dioxide are sintered in ammonium polyphosphate at high temperature to obtain titanium silicoaluminophosphate, which forms a dense mesh structure and wraps around the sheath layer to isolate the air. In addition, nano-titanium dioxide is modified with a mixed solution of silane coupling agent KH-540 and butyl acetate to improve the dispersibility, thereby making the aluminum silicate fiber and titanium dioxide more evenly fused. The network-like titanium silicoaluminophosphate obtained by sintering the two can wrap the sheath layer more evenly and achieve better flame retardant effect.
[0025] In the embodiment of the present invention, the high temperature resistant filling layer includes glass fibers with a length of 1-3 mm and silicon carbide fibers with a length of 50-100 μm; and the mass ratio of glass fibers to silicon carbide fibers is 10-5:5-3. The longer glass fibers form a skeleton, and the shorter silicon carbide fibers are filled into the longer glass fiber skeleton, making the filling layer denser, thereby further improving the high temperature resistance of the filling layer.
[0026] In the embodiment of the present invention, the insulating layer is cross-linked polyethylene; the flame retardant layer includes the following raw materials in parts by weight: 40-50 parts of silicone resin, 20-30 parts of high-density polyethylene, 10-15 parts of ethylene-octene copolymer, 5-10 parts of magnesium hydroxide, and 30-40 parts of glass fiber; the sheath layer includes the following raw materials in parts by weight: 70-50 parts of polyvinyl chloride resin, 5-10 parts of polyurethane elastomer, 20-25 parts of dioctyl phthalate, 25-30 parts of filler, 8-10 parts of stabilizer, 1-3 parts of antioxidant, 1-3 parts of anti-aging agent, and 0.5-1 parts of lubricant; the degree of polymerization of the polyvinyl chloride resin is 1800-2200. In addition, the thickness of the flame retardant layer is 1-1.5mm; the thickness of the sheath layer is 0.5-1mm.
[0027] Another embodiment of the present invention provides a method for preparing a high temperature resistant cable, comprising the following steps: S1. Extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S2, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber to prepare a high temperature resistant filling layer; wherein the mass ratio of the glass fiber to the silicon carbide fiber is 10-5:5-3, and a cable core is obtained after the filling is completed; S3, mixing silicone resin, high-density polyethylene, ethylene-octene copolymer, magnesium hydroxide and glass fiber uniformly, kneading and extruding at 280-310° C., with the extruder speed being 40-50 rpm, and coating the cable core to obtain a flame retardant layer; S4, mixing polyvinyl chloride resin, polyurethane elastomer, dioctyl phthalate, filler, stabilizer, antioxidant, anti-aging agent and lubricant uniformly, kneading and extruding at 180-200° C., with the extruder rotating speed being 40-50 rpm, and coating the flame retardant layer to obtain a sheath layer; S5. When the surface temperature of the sheath layer drops to 30-40℃, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer with a coating thickness of 3-5mm. Then, the sheath layer is irradiated with ultraviolet light with an irradiation intensity of 90-150W / cm 2 The irradiation time is 1-2h, and high temperature resistant cables are obtained after irradiation.
[0028] The present invention will be further described below in conjunction with specific embodiments, but this should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by technicians in this field based on the above-mentioned contents of the present invention still fall within the scope of protection of the present invention.
[0029] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods well known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the common meanings understood by ordinary technicians in the field to which the present invention belongs.
[0030] Example 1
[0031] S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, place it in a polytetrafluoroethylene reactor, and heat it in a 240° C. oven under sealing conditions for 2.5 hours. After cooling, filtering and centrifugation, nano-titanium dioxide crystal particles are obtained; the nano-titanium dioxide crystal particles are washed with ethanol, and then added to a butyl acetate solution mixed with a silane coupling agent KH-540, and heated at 70° C. for 25 minutes to obtain modified nano-titanium dioxide; S2, take 3 parts of nano aluminum silicate fiber, put it into 6 parts of modified nano titanium dioxide under stirring, mix well, then add the mixed solution to a mixed solution of 45 parts of acrylic emulsion, 30 parts of ammonium polyphosphate and 12 parts of pentaerythritol, then add 3 parts of nano silicon dioxide, 1 part of dispersant, 0.5 parts of plasticizer, 0.05 parts of preservative, and ultrasonically disperse for 20 minutes to obtain a high temperature resistant protective coating liquid; S3, extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S4, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber, wherein the mass ratio of glass fiber to silicon carbide fiber is 7:3; S5, 50 parts of silicone resin, 25 parts of high-density polyethylene, 12 parts of ethylene-octene copolymer, 6 parts of magnesium hydroxide, and 32 parts of glass fiber are mixed and extruded at 280° C. The extruder speed is 45 rpm, and the mixture is coated on the cable core to obtain a flame retardant layer; S6, 65 parts of polyvinyl chloride resin with a polymerization degree of 2000, 8 parts of polyurethane elastomer, 23 parts of dioctyl phthalate, 30 parts of filler, 8 parts of stabilizer, 2 parts of antioxidant, 1 part of antioxidant, and 0.8 parts of lubricant are mixed and extruded at 190° C. The extruder speed is 45 rpm, and the mixture is coated on the flame retardant layer to obtain a sheath layer; S7. When the surface temperature of the sheath layer drops to 35°C, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer with a coating thickness of 5mm. Then, the sheath layer is irradiated with ultraviolet light with an irradiation intensity of 120W / cm 2 The irradiation time is 1.5h, and high temperature resistant cables are obtained after irradiation.
[0032] Example 2
[0033] S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, place it in a polytetrafluoroethylene reactor, and heat it in a 220° C. oven under sealing conditions for 3 hours. After cooling, filtering and centrifugation, nano-titanium dioxide crystal particles are obtained; the nano-titanium dioxide crystal particles are washed with ethanol, and then added to a butyl acetate solution mixed with a silane coupling agent KH-540, and heated at 72° C. for 20 minutes to obtain modified nano-titanium dioxide; S2, take 2 parts of nano aluminum silicate fiber, put it into 6 parts of modified nano titanium dioxide under stirring, mix well, then add the mixed solution to a mixed solution of 50 parts of acrylic emulsion, 30 parts of ammonium polyphosphate and 13 parts of pentaerythritol, then add 2 parts of nano silicon dioxide, 0.8 parts of dispersant, 0.8 parts of plasticizer, 0.04 parts of preservative, and ultrasonically disperse for 25 minutes to obtain a high temperature resistant protective coating liquid; S3, extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S4, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber, with the mass ratio of glass fiber to silicon carbide fiber being 9:5; S5, 45 parts of silicone resin, 20 parts of high-density polyethylene, 11 parts of ethylene-octene copolymer, 6 parts of magnesium hydroxide, and 32 parts of glass fiber are mixed and extruded at 290° C. The extruder speed is 40 rpm, and the mixture is coated on the cable core to obtain a flame retardant layer; S6, 70 parts of polyvinyl chloride resin with a polymerization degree of 1800, 8 parts of polyurethane elastomer, 22 parts of dioctyl phthalate, 25 parts of filler, 8 parts of stabilizer, 2 parts of antioxidant, 1 part of antioxidant, and 0.8 parts of lubricant are mixed evenly, kneaded and extruded at 180° C., with the extruder speed being 40 rpm, and coated on the flame retardant layer to obtain a sheath layer; S7. When the surface temperature of the sheath layer drops to 30°C, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer with a coating thickness of 4mm. Then, the sheath layer is irradiated with ultraviolet light with an irradiation intensity of 140W / cm 2 The irradiation time is 2h, and high temperature resistant cables are obtained after irradiation.
[0034] Example 3
[0035] S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, place it in a polytetrafluoroethylene reactor, and heat it in a 250° C. oven under sealing conditions for 2.5 hours. After cooling, filtering and centrifugation, nano-titanium dioxide crystal particles are obtained; the nano-titanium dioxide crystal particles are washed with ethanol, and then added to a butyl acetate solution mixed with a silane coupling agent KH-540, and heated at 80° C. for 20 minutes to obtain modified nano-titanium dioxide; S2, take 2 parts of nano aluminum silicate fiber, put it into 5 parts of modified nano titanium dioxide under stirring, mix well, then add the mixed solution to a mixed solution of 38 parts of acrylic emulsion, 25 parts of ammonium polyphosphate and 15 parts of pentaerythritol, then add 4 parts of nano silicon dioxide, 1.5 parts of dispersant, 0.7 parts of plasticizer, 0.08 parts of preservative, and ultrasonically disperse for 30 minutes to obtain a high temperature resistant protective coating liquid; S3, extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S4, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber, with the mass ratio of glass fiber to silicon carbide fiber being 8:3; S5, 45 parts of silicone resin, 25 parts of high-density polyethylene, 13 parts of ethylene-octene copolymer, 9 parts of magnesium hydroxide, and 32 parts of glass fiber are mixed and extruded at 300° C. The extruder speed is 40 rpm, and the mixture is coated on the cable core to obtain a flame retardant layer; S6, 65 parts of polyvinyl chloride resin with a polymerization degree of 2100, 9 parts of polyurethane elastomer, 24 parts of dioctyl phthalate, 28 parts of filler, 8 parts of stabilizer, 2 parts of antioxidant, 1 part of antioxidant, and 0.7 parts of lubricant are mixed and extruded at 185° C. The extruder speed is 50 rpm, and the mixture is coated on the flame retardant layer to obtain a sheath layer; S7. When the surface temperature of the sheath layer drops to 35°C, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer with a coating thickness of 3mm. Then, the sheath layer is irradiated with ultraviolet light with an irradiation intensity of 100W / cm 2 The irradiation time is 1.5h, and high temperature resistant cables are obtained after irradiation.
[0036] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step S1 is omitted, the high temperature resistant protective coating liquid prepared in step S2 does not contain modified nano titanium dioxide, and the remaining steps are the same as those in Example 1.
[0037] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step S1 is omitted, unmodified nano titanium dioxide is directly added to the high-temperature resistant protective coating liquid prepared in step S2, and the remaining steps are the same as those in Example 1.
[0038] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step S4, during the process of preparing the high temperature resistant filling layer, only glass fiber is added, and the remaining steps are the same as those in Example 1.
[0039] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step S4, during the process of preparing the high temperature resistant filling layer, the mass ratio of glass fiber to silicon carbide fiber is 5:1, and the remaining steps are the same as those in Example 1.
[0040] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in step S7, the coating thickness of the high temperature resistant protective coating is 2 mm, and the remaining steps are the same as those in Example 1.
[0041] Performance Testing The high temperature resistant cables prepared in Examples 1-3 and Comparative Examples 1-4 were cut into 1.2 m lengths and subjected to the following tests.
[0042] Oxygen index: The combustion behavior is determined according to the oxygen index method for plastics in accordance with GB_T 2406.2-2009.
[0043] Fire resistance: According to GB / T 19216.2-2021 Line integrity test for cables or optical cables under flame conditions Part 2: Fire with a flame temperature of not less than 830 °C and impact vibration, test method for cables with a rated voltage of 0.6 / 1kV and below and an outer diameter not exceeding 20 mm, the test cable length is 1.2m, the voltage is 380v, and the impact generating device is started after the blowtorch is ignited. After 5 minutes and every 5 minutes thereafter, knock on the test ladder. Each time the knocking rod is lifted from the test ladder within 20 seconds after knocking, turn on the power after the timer starts. The fire supply and knocking time is 90 minutes. Determine whether the power supply can be sustained based on the indication of the terminal indicator light. If it goes out within 30 minutes, the fire resistance level is judged to be V3. If it goes out within 30-60 minutes, the fire resistance level is judged to be V2. If it goes out within 60-90 minutes, the fire resistance level is judged to be V1. If it does not go out within 90 minutes, the fire resistance level is judged to be V0, where V0 indicates the best fire resistance performance, V1 is the second, and V3 is the worst. The test results are shown in Table 1.
[0044] Table 1 Fire performance test results Oxygen index LOI / % Fire resistance level Example 1 43 V0 Example 2 41 V0 Example 3 42 V0 Comparative Example 1 38 V2 Comparative Example 2 40 V1 Comparative Example 3 39 V2 Comparative Example 4 42 V1 Comparative Example 5 41 V1 It is not difficult to see from the above test results that the high temperature resistant cable prepared in Example 1 of the present invention has the highest oxygen index, the highest fire resistance grade of V0, and the best high temperature resistant flame retardant performance; while the flame retardant effect of the cable prepared without adding modified nano titanium dioxide, nano titanium dioxide without modification or without adding silicon carbide is slightly worse than that of Example 1; and the thickness of the high temperature resistant coating also has a certain degree of influence on the fire resistance. It can be seen from Comparative Example 5 that when the high temperature resistant coating is 2mm, the fire resistant flame retardant performance of the cable is lower than that of the high temperature resistant cable in Example 1. In summary, the high temperature resistant cable proposed by the present invention has excellent high temperature resistance and flame retardant performance.
[0045] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A high temperature resistant cable, characterized in that: From the inside to the outside, it includes a cable core, a flame retardant layer and a sheath layer; the cable core is composed of multiple insulated wire cores arranged in parallel and longitudinally in a high temperature resistant filling layer, the surface of the insulated wire core is in close contact with the high temperature resistant filling layer, and is coated in the high temperature resistant filling layer; the insulated wire core includes a cable obtained by winding a plurality of wires, and an insulating layer coated on the outside of the cable; The sheath layer also includes a high temperature resistant protective coating coated on its outer surface; The high temperature resistant protective coating comprises the following raw materials in parts by weight: 30-50 parts of acrylic emulsion, 25-40 parts of ammonium polyphosphate, 10-15 parts of pentaerythritol, 1-5 parts of nano aluminum silicate fiber, 5-10 parts of modified nano titanium dioxide, 1-5 parts of nano silicon dioxide, 0.5-2 parts of dispersant, 0.5-1 parts of plasticizer, and 0.01-0.1 parts of preservative; The modified nano titanium dioxide preparation method comprises the following steps: S1. Take tetrabutyl titanate and add it to the n-hexanoic acid solution. After mixing evenly, put it in a polytetrafluoroethylene reactor. Under sealed conditions, put it in an oven at 220-250° C. and heat it for 2.5-3 hours. After cooling, filtering and centrifugation, obtain nano-titanium dioxide crystal particles; S2. Wash the nano-titanium dioxide crystal particles obtained in step S1 with ethanol, then add them into a butyl acetate solution mixed with a silane coupling agent KH-540, and heat them at 65-80° C. for 20-30 min to obtain modified nano-titanium dioxide.
2. The high temperature resistant cable according to claim 1, characterized in that: The mass ratio of the nano aluminum silicate fiber to the modified nano titanium dioxide is 1-2:2-6.
3. The high temperature resistant cable according to claim 1, characterized in that: The thickness of the high temperature resistant protective coating is 3-5 mm.
4. The high temperature resistant cable according to claim 1, characterized in that: The high temperature resistant filling layer comprises glass fiber and silicon carbide fiber; the mass ratio of the glass fiber to the silicon carbide fiber is 10-5:5-3.
5. The high temperature resistant cable according to claim 4, characterized in that: The glass fiber has a length of 1-3 mm, and the silicon carbide fiber has a length of 50-100 μm.
6. The high temperature resistant cable according to claim 1, characterized in that: The insulating layer is cross-linked polyethylene.
7. The high temperature resistant cable according to claim 1, characterized in that: The flame retardant layer comprises the following raw materials in parts by weight: 40-50 parts of organic silicone resin, 20-30 parts of high-density polyethylene, 10-15 parts of ethylene-octene copolymer, 5-10 parts of magnesium hydroxide, and 30-40 parts of glass fiber.
8. The high temperature resistant cable according to claim 1, characterized in that: The sheath layer comprises the following raw materials in parts by weight: 50-70 parts of polyvinyl chloride resin, 5-10 parts of polyurethane elastomer, 20-25 parts of dioctyl phthalate, 25-30 parts of filler, 8-10 parts of stabilizer, 1-3 parts of antioxidant, 1-3 parts of anti-aging agent, and 0.5-1 parts of lubricant; the polymerization degree of the polyvinyl chloride resin is 1800-2200.
9. The high temperature resistant cable according to claim 1, characterized in that: The thickness of the flame retardant layer is 1-1.5 mm; the thickness of the sheath layer is 0.5-1 mm.
10. The method for preparing a high temperature resistant cable according to any one of claims 1 to 9, characterized in that: The steps include: S1. Extruding cross-linked polyethylene onto the outside of a cable obtained by winding a plurality of conductors to obtain an insulated core; S2, placing multiple insulated wire cores spaced apart and parallel to each other, and filling them with glass fiber and silicon carbide fiber to prepare a high temperature resistant filling layer; wherein the mass ratio of the glass fiber to the silicon carbide fiber is 10-5:5-3, and a cable core is obtained after the filling is completed; S3, mixing silicone resin, high-density polyethylene, ethylene-octene copolymer, magnesium hydroxide and glass fiber uniformly, kneading and extruding at 280-310° C., with the extruder speed being 40-50 rpm, and coating the cable core to obtain a flame retardant layer; S4, mixing polyvinyl chloride resin, polyurethane elastomer, dioctyl phthalate, filler, stabilizer, antioxidant, anti-aging agent and lubricant uniformly, kneading and extruding at 180-200° C., with the extruder rotating speed being 40-50 rpm, and coating the flame retardant layer to obtain a sheath layer; S5. When the surface temperature of the sheath layer drops to 30-40°C, evenly apply the high temperature resistant protective coating liquid to the surface of the sheath layer, and then irradiate the sheath layer with ultraviolet light at an intensity of 90-150W / cm 2 The irradiation time is 1-2h, and high temperature resistant cables are obtained after irradiation.
Citation Information
Patent Citations
Steelwork fire-retardant paint using self-crosslinking silicone-acrylic compound emulsion as substrate and preparation thereof
CN101205441A
Cable and production process thereof
CN105968698A
Glass fiber-based reinforced fibers for silica aerogel
CN108383488A
High-flexibility low-smoke modified power cable based on fluoropolymer sheath and preparation method
CN117976314A
PVC cable sheath material and preparation method thereof
CN117986773A
